2015
DOI: 10.1002/hed.24307
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of squamous cell carcinoma of the posterior pharyngeal wall: Radiotherapy versus surgery

Abstract: Surgical management translated into a survival benefit, even in early T classification. These results should be interpreted with caution for selection bias. Surgery remains the standard of care in localized posterior pharyngeal wall SCC. Primary CRT should be considered for nonoperable disease. © 2015 Wiley Periodicals, Inc. Head Neck 38: E1722-E1729.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The prolonged gastrostomy was reported to be significantly associated with T3‒T4 disease at initial diagnosis in a series, but it was found that there was no significant difference between the primary RT/CRT group and the surgical treatment group regarding the gastrostomy or tracheostomy presence beyond 1 year. 15 In our patients, the swallowing function recovered within a mean time of 75 days and the subjective evaluation of the quality of swallowing by EAT-10 and FOIS was satisfactory.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The prolonged gastrostomy was reported to be significantly associated with T3‒T4 disease at initial diagnosis in a series, but it was found that there was no significant difference between the primary RT/CRT group and the surgical treatment group regarding the gastrostomy or tracheostomy presence beyond 1 year. 15 In our patients, the swallowing function recovered within a mean time of 75 days and the subjective evaluation of the quality of swallowing by EAT-10 and FOIS was satisfactory.…”
Section: Discussionsupporting
confidence: 48%
“…The authors concluded that these findings suggest a survival advantage of combined treatment with surgery and adjuvant radiation. 11 Moreover, in a study specifically about posterior pharyngeal wall carcinomas, 15 De Felice et al reported that 5 year local control was significantly higher in the primary surgery group compared with RT/CRT in both T1‒T2 (96.7% vs. 55.8%) and T3‒T4 diseases (73% vs. 52.7%). A significant Overall Survival (OS) benefit for 5 year was obtained with surgical treatment compared to RT/CRT in T1‒T2 diseases (63.8% vs. 39.7%), whereas OS in T3‒T4 diseases were not significantly different between surgery and RT/CRT arms (29.5% vs. 20.3%).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported the prognostic role of hypopharyngeal carcinoma subsites. For example, Asakage et al reported a high rate of distant metastasis in postcricoid carcinoma, whereas De Felice et al reported that the treatment outcomes of pharyngeal wall carcinoma remain poor compared with those of carcinomas at other head and neck subsites because of the rich submucosal lymphatics of the pharyngeal wall.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study on the treatment of LSCC has focused on the comparison between primary radiotherapy and CRT (12), and there have been few studies performed to compare surgery and surgery + adjuvant CRT for patients with advanced LSCC. The aim of the present study was to determine the clinical effect of adjuvant CRT for patients with advanced LSCC who underwent initial surgeries in a single institution over a 10-year post-treatment follow-up.…”
Section: Introductionmentioning
confidence: 99%